Complement C3a signaling facilitates skeletal muscle regeneration by regulating monocyte function and trafficking - Congcong Zhang (Nature Portfolio, 2017)
Regeneration of skeletal muscle is accompanied by a transitory inflammatory phase. Here the authors show that the complement C3 component is activated following muscle injury, and signals through the alternative complement pathway to regulate immune cell infiltration and muscle regeneration.